Sustainable crop-livestock production for improved livelihoods and natural resource management in West Africa. Proceedings of an international conference - Williams, Timothy O.; Tarawali, Shirley A.; Hiernaux, Pierre H.Y.; Fernández Rivera, S. (International Livestock Research Institute, 2004)
This conference was conducted to review the development of crop-livestock farming systems in West Africa over the preceding two decades with particular reference to the constraints, productivity, livelihood and environmental impacts; to assess future trends and determine new opportunities for sustainable intensification of crop-livestock systems; to identify research priorities and collaborative mechanisms to foster improved productivity, natural resource management and livelihoods of crop-livestock producers in West Africa. This volume presents a subset of papers presented at the conference. It is divided into four parts. Part I presents background papers that examine the impacts of population pressure, agroecology and economic policies on the evolution of crop-livestock systems and draws implications for future development of these systems. Part II begins with a comparative analysis of crop-livestock systems in West Africa, Asia and Latin America and goes on to present various research results and natural resource management options used by smallholder farmers, carefully drawing out implications for the future development of crop-livestock systems in West Africa. Papers in Part III examine future trends and emerging opportunities in Science, economic environment and research collaboration and emerging opportunities in science, economic environment, and research collaboration and discusses how these can be exploited to foster sustainable intensification of crop-livestock systems. Part IV includes two short papers that demonstrate the relevance of farmers' ethno-veterinary and soil fertility knowledge in the design and evaluation of new technologies and management practices.. The volume is a blend of studies focusing on site-specific factors, processes and wider policy options which, appropriately combined, can improve the productivity and sustainability of crop-livestock systems in West Africa and other regions with similar characteristics.